Spatial resolution and velocity field improvement of 4D‐flow MRI. Issue 5 (24th November 2016) - Callaghan, Fraser M.; Grieve, Stuart M.
Abstract : Purpose: 4D‐flow MRI obtains a time‐dependent 3D velocity field; however, its use for the calculation of higher‐order parameters is limited by noise. We present an algorithm for denoising 4D‐flow data. Theory and Methods: By integrating a velocity field and eliminating streamlines in noisy flow, depicted by high curvature, a denoised dataset may be extracted. This method, defined as the velocity field improvement (VFIT) algorithm, was validated in an analytical dataset and using in vivo data in comparison with a computation fluid dynamics (CFD) simulation. As a proof of principal, wall shear stress (WSS) measurements in the descending aorta were compared with those defined by CFD. Results: The VFIT algorithm achieved a >100% noise reduction of a corrupted analytical dataset. In addition, 4D‐flow data were cleaned to show improved spatial resolution and near wall velocity representation. WSS measures compared well with CFD data and bulk flow dynamics were retained (<2% difference in flow measurements). Conclusion: This study presents a method for denoising 4D‐flow datasets with improved spatial resolution. Bulk flow dynamics are accurately conserved while velocity and velocity gradient fields are improved; this is important in the calculation of higher‐order parameters such as WSS, which are shown to be more comparable to CFD measures. Magn Reson Med 78:1959–1968, 2017. © 2016 International Society for Magnetic Resonance in Medicine.